Modernization and Refomism in the Development of Islamic Law and Social Institutions: A Case Study of Islamic Law Application - Billah, Muktashim; Gassing HT, Abdul Qadir (Journal of Family Law and Islamic Court, 2022)
Islam as a solutive religion that is a blessing for all humans, one form of mercy is by giving Islamic law to humans. The application of Islamic law was carried out starting at the time of the Prophet. become a leader for Muslims, to this day even though the intensity of its application is different. There are two major countries that include Islamic law in their laws. Even though it is included in the law, there are different legal approaches that give birth to Islamic law that is unique in each region, therefore it is necessary to study modernization and reformism in the development of Islamic law and social institutions, its challenges and cases. The study was carried out in the literature and concluded that in the realm of ijtihad it is permissible to carry out legal reforms as long as it is based on the basis of the text, even though there are many challenges because the struggle is related to politics.